How to conduct consistent environmental, economic, and social assessment during the building design process. A BIM-based Life Cycle Sustainability Assessment method. (January 2022) - Soust-Verdaguer, B.; Bernardino Galeana, I.; Llatas, C.; Montes, M.V.; Hoxha, E.; Passer, A.
Abstract: The built environment is significantly responsible for the current climate crisis, thus developing more sustainable projects is becoming an urgent objective. One widely recognized method that supports achieving this objective is the Life Cycle Sustainability Assessment (LCSA), which enables a holistic, quantitative evaluation of building sustainability, including environmental, economic, and social dimensions. The integration of this method in digital design tools such as Building Information Modelling (BIM) facilitates its use during the building design stages. However, data granularity is not the same in every design stage, and consequently data consistency cannot be assured. Hence, the margin of unexpected variation of the results shall be avoided and robust results from the early design stages should be obtained. During the early stage, the level of details is generally limited to the element definition, while during the detailed stages, the volume of information regarding the building increased. This paper aims to fill in the informational gaps during the early design stage and align those results with a detailed data structure developed for cost estimation during the detailed stages. Thus, based on a case study analysis, we can demonstrate the consistency of the method by determining the variation of material quantities and comparing the LCSA inventory indicators during the early and detailed stages. This method can estimate more than 60% of the LCSA inventory indicators during the early design stage and the total results during detailed design stage. Highlights: Method to align cost estimation data structure with element Open BIM workflow is proposed. Information gaps for conducting LCSA in BIM at early design stages are filled. Case study is used to compare the LCSA results at the early and detailed design stages. More than 60% of the LCSA total results can be estimated at the early design stage. Structure, envelope, and finishing are the most relevant building systems for potential optimization.